PROSPECTS OF ADMINISTRATIVE AND LEGAL REGULATION OF PROPERTY AND FOOD SUPPLY OF THE ARMED FORCES OF UKRAINE - Piskun, Ivan; Voznyk, Mykhaylo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to study the prospects of administrative and legal regulation of material and food security of the Armed Forces of Ukraine, to analyze the process of military law-making, by analyzing published documents and materials on bringing military legislation to international standards. Methods: are the main methods and means of cognition, such as: documentary analysis and synthesis, comparison, objective truth, cognitive-analytical, intersectoral method of legal research, generalization. Results: outlines the implementation of NATO standards in the functioning of Ukraine's security and defense sector through the use of post-Soviet principles. It has been proved that the implementation of NATO standards in the practice of the Armed Forces of Ukraine is an important task that requires a comprehensive review and updating of the legal framework for establishing appropriate cooperation. Discussion: development and implementation of regulations on the implementation of international standards governing the logistics of the Armed Forces of Ukraine, will improve the efficiency of state resources in the field of defense, improve the training of military units and units that are part of multinational military formations, as well as growth authority of Ukraine in the international arena. The ongoing armed conflict has significantly intensified the renewal ofmilitary legislation, as new threats are constantly emerging, objectively necessitating the search for adequate ways to counter, including through deep transformation of the structure of the Armed Forces of Ukraine, achieving interoperability with NATO forces. Therefore, no less important is the legislative support of the reform process of the Armed Forces of Ukraine, creating the necessary conditions for the adaptation of legislative, conceptual and doctrinal documents to NATO standards, as noted in the National Security Strategy of Ukraine and Military Doctrine of Ukraine. The direction of further reform should also be to improve the mechanism for providing social guarantees for servicemen in Ukraine, taking into account foreign experience. Social security of servicemen is a system of economic and legal measures aimed at the state to provide servicemen with the appropriate level of financial, medical, housing, material, food and other types of support to ensure their livelihoods, given the complexity of special tasks. Ukraine has established the basic legal framework for the implementation of NATO standards in the functioning of the Armed Forces of Ukraine and there is a steady trend to continue working in this direction. The most urgent task of norm-setting for the introduction of NATO standards in the functioning of the Armed Forces of Ukraine should be the development of regulatory mechanisms to accelerate technical re-equipment of units of the Armed Forces of Ukraine, optimize the military command of military bodies, units and units.